Firmness Evaluation Of Watermelon Using Acoustic Method - Muhammad Aqil Bin Zulkifli (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Firmness is one of the most important criteria in terms of quality in watermelon grading. Firmness can be used to indicate the ripeness of the watermelon fruit. The firmness evolution of fruit during storage enabled the producers to manage the storing time and fruit freshness before heading out to consumer. Currently, the most reliable method is by tapping the fruit. Experience workers will tap the fruit and hear the sound produced when the fruit is being hit. Immature fruit will produce metallic ringing sound while mature fruit will produce hollow or dull sound. This project aims to develop a measurement system using acoustic method to measure the watermelon fruit firmness mimicking the tapping of the fruit by experience worker. The measurement system uses solenoid to mimicking the tapping of the fruit and microphone to mimic the ears of the experience worker. The measurement system gather the acoustic impulse produce by the fruit once the fruit being hit and evaluate the firmness index (S). Once the measurement system is developed, the evolution of watermelon fruit during storage in 15 days periods was assessed based on the firmness index over number of days. The firmness index of the watermelons decrease as the day goes by at the rate of 0.0856 kg/day. The range value of firmness is between 1.0 〖10〗^5 to 4.5 〖10〗^5 〖kg〗^(2/3) s^(-2). Besides that, the hardness and the sweetness level of the watermelons was also evaluated. The hardness of the watermelon show a decrease in trend which are similar to firmness. The range value of hardness is between 4400 to 5550 g. For the sweetness level, the sweetness of the watermelons decrease over time but they are not conclusive. The correlation between firmness and hardness was also evaluated and it seems there is a worthwhile relationship between them